2011
DOI: 10.1038/ejcn.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breakfast glycemic index on metabolic responses during rest and exercise in overweight and non-overweight adolescent girls

Abstract: Background/Objectives: The metabolic responses to mixed breakfast meals with different glycemic indexes (GI) and their effects on substrate metabolism during exercise in adolescent girls have not been examined. The interaction with weight status also warrants investigation. This study investigated the effect of mixed breakfast meals containing high GI (HGI) or low GI (LGI) carbohydrates on metabolic responses and fat oxidation during rest and exercise in overweight (OW) and non-overweight (NO) adolescent girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
10
0
2
Order By: Relevance
“…In line with previous research using similar mixed breakfast meals (Stevenson et al 2009; Zakrzewski et al 2012), the high GI breakfast induced a larger glucose response compared with the low GI breakfast. Somewhat unexpectedly, the postprandial peak in glucose and insulin concentrations was higher in the low GI compared with the high GI breakfast conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous research using similar mixed breakfast meals (Stevenson et al 2009; Zakrzewski et al 2012), the high GI breakfast induced a larger glucose response compared with the low GI breakfast. Somewhat unexpectedly, the postprandial peak in glucose and insulin concentrations was higher in the low GI compared with the high GI breakfast conditions.…”
Section: Discussionsupporting
confidence: 90%
“…There have been a limited number studies testing the effects of breakfast macronutrient composition on satiety and subsequent food intake in 8-to 12-y-old children, with most studies focusing on the role of glycemic index at breakfast (19,(35)(36)(37)(38). A majority of the studies that have been conducted are in a preschool population and examine the difference of glycemic index on satiety and food intake and not macronutrient distribution of the breakfast (18,19).…”
Section: Discussionmentioning
confidence: 95%
“…As a common breakfast food, it is possible that RTEC consumption is a proxy for breakfast consumption in general. Other studies have considered macronutrient composition and glycemic index; although experimental studies have found some potential short‐term metabolic and eating behaviour benefits of breakfasts high in protein and/or low in glycemic index/load, evidence is mixed and relationships with anthropometric outcomes unsubstantiated .…”
Section: Discussionmentioning
confidence: 99%